2010
DOI: 10.1105/tpc.109.071001
|View full text |Cite
|
Sign up to set email alerts
|

Plastidial Thioredoxin z Interacts with Two Fructokinase-Like Proteins in a Thiol-Dependent Manner: Evidence for an Essential Role in Chloroplast Development in Arabidopsis and Nicotiana benthamiana    

Abstract: Here, we characterize a plastidial thioredoxin (TRX) isoform from Arabidopsis thaliana that defines a previously unknown branch of plastidial TRXs lying between x-and y-type TRXs and thus was named TRX z. An Arabidopsis knockout mutant of TRX z had a severe albino phenotype and was inhibited in chloroplast development. Quantitative real-time RT-PCR analysis of the mutant suggested that the expressions of genes that depend on a plastid-encoded RNA polymerase (PEP) were specifically decreased. Similar results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
359
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(372 citation statements)
references
References 90 publications
12
359
0
1
Order By: Relevance
“…S9) (42, 43). Arsova et al demonstrated that Trx-z binds to two fructokinase-like proteins (FLNs) in a thiol-dependent manner, which is essential for plastid-encoded RNA polymerase (PEP)-dependent gene expression and proper chloroplast development (42). In accordance with this report, Trx-z and FLNs were identified as PEP complex components by proteomic studies (44,45).…”
Section: Ntrc and Five Trx Subtypes Differentially Recognize Target Psupporting
confidence: 70%
“…S9) (42, 43). Arsova et al demonstrated that Trx-z binds to two fructokinase-like proteins (FLNs) in a thiol-dependent manner, which is essential for plastid-encoded RNA polymerase (PEP)-dependent gene expression and proper chloroplast development (42). In accordance with this report, Trx-z and FLNs were identified as PEP complex components by proteomic studies (44,45).…”
Section: Ntrc and Five Trx Subtypes Differentially Recognize Target Psupporting
confidence: 70%
“…The CC-type class expanded exclusively and strongly during the evolution of land plants, suggesting that this class of GRXs might have been recruited to participate in the evolution of more complex land plants (Xing et al, 2006;Ziemann et al, 2009). Contrasting with wide-ranging roles of plant thioredoxins in chloroplast and mitochondrial processes, seed development and germination, and auxin signaling (Buchanan and Balmer, 2005;Reichheld et al, 2007;Arsova et al, 2010;Bashandy et al, 2010), the biological and physiological functions of plant GRXs have remained largely elusive. Recently, two CC-type GRX genes, ROXY1 and ROXY2, were functionally characterized, revealing their functions during Arabidopsis flower development Xing and Zachgo, 2008;).…”
mentioning
confidence: 99%
“…1C). This distinct location of pTAC14 is reminiscent of reports of thylakoid-associated proteins, including MPF1 (Jeong et al, 2003), PEND (Terasawa and Sato, 2009), sulfite reductase (Sekine et al, 2007), CND41 (Murakami et al, 2000), and other characterized TAC components, such as FSD3 , FLN1, and FLN2 (Arsova et al, 2010). These proteins were suggested to be tightly associated with plastid nucleoids.…”
Section: Discussionmentioning
confidence: 92%
“…pTAC14 Regulates PEP Activity in Chloroplast like those that are detected in other TAC mutants, such as ptac6 and ptac12 (Pfalz et al, 2006), atmurE (Garcia et al, 2008), trxz (Arsova et al, 2010), fln1 (Arsova et al, 2010), and fsd2 and fsd3 . Similarly, differently sized vesicles can be observed in the chloroplasts of these mutants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation